COMPUTER- AIDED MODELING AND IMPROVING OF RISOGRAPH PRINTING - P. E. Sulim; V. S. Yudenkov (Системный анализ и прикладная информатика)
The considered improvement of qualit y of the risofraph print based on a mathematical model in the environment Matlab by using the specialized algorithms and digital filter of the Image Processing Toolbox. Use the model of screen printing in Matlab environment for risograph provide an opportunit y to improve the qualit y of prints by adjusting profile risograph to a specific view and the t ype of digital image. The use of the proposed technology will reduce the flow of the film and the paint by eliminating printing test prints and reducing the time spent printing.